The impact of tourism development among Batek community in Taman Negara Kuala Koh, Kelantan - Wan Mohd Radzi, Wan Mohamad Izwan (2018)
The development of the tourism industry in Taman Negara Kuala Koh, Kelantan has brought many positive impacts directly or indirectly to the local community, including the indigenous people. The main purpose of the study is to analyse the socio-economics and environmental impacts upon the Batek community as a result of tourism development in Taman Negara Kuala Koh, Kelantan. This analysis is based on their perceptions on three aspects of tourism development; which are the economic, social and environmental issue. Face to face interviews were conducted with 12 identified respondents in the month of March 2018. Research findings showed that development of tourism industry in Taman Negara Kuala Koh, Kelantan has created positive and negative impacts on the social, economic and environmental aspects of the Batek communities.